Synthesis and Aggregation of Amphiphilic Porphyrin-Perylenebisimide Dyads - Schulze, Erik; Wu, Mingjian; Methfessel, Christian; Spiecker, Erdmann; Hirsch, Andreas (Chemistry - A European Journal, 2025)
We report the straightforward synthesis of a family of amphiphilic zinc-porphyrin-perylenebisimide (PBI) dyads containing sterically demanding substituents at the porphyrin meso-position, as well as at the PBI bay-position. The hydrophilic head group consists of oligo-carboxylic acid G2-Newkome dendrons attached to the porphyrin, whereas lipophilic pentyl-hexyl-swallowtails are connected to the PBI imide position. Using UV/Vis absorption and fluorescence emission spectroscopy, their tetrahydrofuran (THF) initiated disaggregation was studied in aqueous media. Without meso-substituents, a stronger interaction between the porphyrins was observed in the aggregated state. Insights into the size and morphology of the aggregates were obtained by dynamic light scattering (DLS) and scanning transmission electron microscopy (STEM). Supported by density functional theory (DFT) calculations, these revealed micelles and liposomes as plausible architectures.
CRIS-Team Scopus Importer:2025-05-16
Keywords: aggregation; amphiphiles; donor-acceptor-hybrids; perylenebisimide; porphyrinoids